A Possible Monastery and the ‘Upper Maqs’ at Ukma-Akasha West? - Edwards, David N. (Études et Travaux, 2019)
This paper summarises previously unpublished records relating to a series of unusual, and perhaps associated enclosed medieval settlements in the area of Akasha and Ukma West, excavated in 1969 by the Archaeological Survey of Sudanese Nubia. When excavated, one site, namely [21-N-11], which contained a small church, was thought likely to have been a monastery. An unusual site close by is also briefly discussed. Two other enclosed sites, and perhaps a further uncompleted example, have some features in common with the putative monastic site, although other functions may be considered. That some of these might relate to the historically recorded government ‘customs post’, the ‘Upper Maqs’, is also possible. While definitive identifications are not possible, a number of features of these sites, which cannot be easily paralleled elsewhere in Nubia, suggest their wider interest, and that they merit further study.